(3GdfLG def GJHY GdgOi hGLJfH GdQOis - (3GdfGUQ dOjf Gddg CMeO Hf GdgGOj Gdj GdMb jMji Hf GdMSjfs
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjMhjg bWQ , hdG jZfjg OgQ , hdG jLQi Ydjg YUQ s
(3BNQgG (B:s
(3hGdhLg GdQGHY (B: (3GdcaQ gfG (B: (3GdHQG (B[ (3GdJHQi (B] (3aPdc bhd EHQGgje aGage Pdc Je cJGH GdfLGI s
(3GdfSNI HgG MhGTs
(3hgh cJGH ai EKHGJ GdYOd hGdQO Ydi YHO Gddg Hf jRjO GdHZOGOi GdeLHQs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg GdLGeY GdcHjQ HUfYGA (B((3Yde GdcdGe (B141) s
Keywords: (3GdJhMjO hGdedd hGdfMds